Reflection of local cultural values behind loss accounting practices by ilabulo sellers - Mohamad Anwar Thalib (Goodwood Publishing, 2023)
Purpose: This study aims to reveal the non-material value behind the practice of loss accounting by ilabulo traders. Methodology/approach: This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. Results/findings: The study results show that traders avoid losses by distributing the leftover ilabulo to the local community for free. This accounting practice is conditional on the value of patience. In the Islamic culture of Gorontalo, the elders often internalize the value of patience through lumadu